Exile and patriotic representations in Gustavo Pérez-Firmat's El año que viene estamos en Cuba - Moukouti Onguédou, Georges (Romanica Olomucensia, 2015)
Exile is the fact that someone leaves his country, voluntarily or involuntarily. In the case of involuntary exile (which is our concern here), some coercive forces oblige a person to abandon his homeland and seek refuge or asylum in another country. Ascunce sees expulsion or forced departure from the fatherland as one of the defining principles of the phenomenon of exile. This implies the persecution of a person for political or religious reasons. Exile, therefore, becomes an allegory of the socio-political history of the expatriate's country and personal and collective memory, whereas the lost homeland becomes the focus of disputes and spatio-mental, spatiotemporal, and cultural representations. This is actually what happens in the autobiographical chronicle El año que viene estamos en Cuba (1997), by the Cuban-American Gustavo Perez-Firmat - this is the translation by the author himself of the English original Next year in Cuba, published in 1994; his family were forced to leave their native Cuba for the US in 1960, following the violent changes to political institutions driven by Fidel Castro after the triumph of the Revolution in 1959. In this paper, the ideas and images that denote and connote the emotional ties of the expatriate with his country are highlighted. How, consciously or unconsciously, some exiles in particular are corroded by nostalgia and strongly tempted by their homeland is also observed. As the writer put it himself, exile is "mutilation" or traumatic separation. Therefore a person who lives in such a situation constantly attempts to recover that missing part of himself, hence the reconstruction of the discourse about the lost homeland.
Keywords: United States; Cuba; exile; patriotism; representations.